Single cell RNA‐seq in the sea urchin embryo show marked cell‐type specificity in the Delta/Notch pathway. Issue 8 (14th June 2019) - Foster, Stephany; Teo, Yee Voan; Neretti, Nicola; Oulhen, Nathalie; Wessel, Gary M.
Abstract: Sea urchin embryos are excellent for in vivo functional studies because of their transparency and tractability in manipulation. They are also favorites for pharmacological approaches since they develop in an aquatic environment and addition of test substances is straightforward. A concern in many pharmacological tests though is the potential for pleiotropic effects that confound the conclusions drawn from the results. Precise cellular interpretations are often not feasible because the impact of the perturbant is not known. Here we use single‐cell mRNA (messenger RNA) sequencing as a metric of cell types in the embryo and to determine the selectivity of two commonly used inhibitors, one each for the Wnt and the Delta‐Notch pathways, on these nascent cell types. We identified 11 distinct cell types based on mRNA profiling, and that the cell lineages affected by Wnt and Delta/Notch inhibition were distinct from each other. These data support specificity and distinct effects of these signaling pathways in the embryo and illuminate how these conserved pathways selectively regulate cell lineages at a single cell level. Overall, we conclude that single cell RNA‐seq analysis in this embryo is revealing of the cell types present during development, of the changes in the gene regulatory network resulting from inhibition of various signaling pathways, and of the selectivity of these pathways in influencing developmental trajectories. Abstract : Through single cell, mRNA‐seq (drop‐seq) approaches we find specificity and distinct effects of the Wnt and Delta/Notch pathways in differential cell lineages. The results illuminate how these conserved pathways selectively regulate cell fates at a single cell level. Overall, we conclude that single cell RNA‐seq analysis in this embryo is revealing of the cell types present during development, of the changes in the gene regulatory network resulting from inhibition of various signaling pathways and of the selectivity of these pathways, in influencing developmental trajectories.